'A pleasant tragicomedy, the cat being scap't'?: William Sampson's The Vow Breaker (1636) and the instability of genre. Issue 2 (4th May 2018) - Grant, Teresa
Abstract: William Sampson's 1636 play The Vow Breaker presents us with what looks like generic confusion: a cat (of all the creatures the least likely to stick to the script) seems to offer us comic relief in a play which, though intended as tragedy, descends into melodramatic sub-Kydian fustian. This essay discusses how the genre of early modern drama is affected by the employment of cats as actors, focusing on Sampson's play which seeks to consolidate tragic effect by emphasising the parallels between a persecuted or helpless animal and the tragic protagonist, in the person of Ann. The cat in the original production was almost certainly real (though we can't prove this), and the essay will argue that tone and genre are crucially influenced by this casting decision. The play is rescued from its fustian, made more troubling, by the uncomfortable stage effects resulting from its feline performer. The essay interacts with Nicholas Ridout's reading of the 'affect' of real animals on the stage, arguing, though, that the early modern stage cat resists a clash between semiotics and phenomenology by not conforming to Ridout's competing binaries. Ridout argues – following Vidal-Naquet – that 'sacrifice is intrinsic to tragic form'. In The Vow Breaker neither sacrificial victim accepts her fate willingly, and it is this return to the pre-tragic, 'known of old' as Freud might have it – holy, wild, live, phenomenal, magic – which Sampson struggles to contain. The final act of the play seeks to restore the ritual of tragedy, disturbed by the various uncontrollable variables in the main plot, by means of ritual animal disguise and by the effacing of the pre-tragic and the feminine.